ON HEAT SOURCE IN SUBDUCTION ZONE - A. A. Kirdyashkin; A. G. Kirdyashkin; V. E. Distanov; I. N. Gladkov (Геодинамика и тектонофизика)
The subduction of an oceanic plate is studied as the motion of a high-viscosity Newtonian fluid. The subducting plate spreads along the 670-km depth boundary under the influence of oppositely directed horizontal forces. These forces are due to oppositely directed horizontal temperature gradients. We consider the flow structure and heat transfer in the layer that includes both the oceanic lithosphere and the crust and moves underneath a continent. The heat flow is estimated at the contact between the subducting plate and the surrounding mantle in the continental limb of the subduction zone. Our study results show that the crustal layer of the subducting plate can melt and a thermochemical plume can form at the 670-km boundary. Our model of a thermochemical plume in the subduction zone shows the following: (1) formation of a plume conduit in the crustal layer of the subducting plate; (2) formation of a primary magmatic chamber in the area wherein the melting rate equals the rate of subduction; (3) origination of a vertical plume conduit from the primary chamber melting through the continent; (4) plume eruption through the crustal layer to the surface, i.e. formation of a volcano. Our experiments are aimed to model the plume conduit melting in an inclined flat layer above a local heat source. The melt flow structure in the plume conduit is described. Laboratory modeling have revealed that the mechanisms of melt eruption from the plume conduit differ depending on whether a gas cushion is present or absent at the plume roof.